2015
DOI: 10.2151/jmsj.2015-006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Northwest Pacific Tropical Cyclone Genesis by the Intraseasonal Variability

Abstract: The modulation of tropical cyclone (TC) genesis over the western North Pacific (WNP) by the intraseasonal variability (ISV) is investigated in this study. The two leading ISV modes, i.e., the 40-day Madden-Julian oscillation (MJO) and the 16-day quasi-biweekly oscillation, are found to exert significant impacts on TC genesis over the WNP. A majority of TC geneses over the WNP is found to occur during the period when both the modes are active, suggesting a joint influence of the two modes on TC genesis over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 76 publications
3
65
0
Order By: Relevance
“…Followup studies further indicated that the enhanced mid-level relative humidity and low-level cyclonic vorticity are the most important factors in modulating the location and frequency of TC genesis (e.g., Camargo et al 2007Camargo et al , 2009Jiang et al 2012;Zhao et al 2015aZhao et al , b, 2017Zhao and Wu 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Followup studies further indicated that the enhanced mid-level relative humidity and low-level cyclonic vorticity are the most important factors in modulating the location and frequency of TC genesis (e.g., Camargo et al 2007Camargo et al , 2009Jiang et al 2012;Zhao et al 2015aZhao et al , b, 2017Zhao and Wu 2017).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the ISV plays an important role in TC genesis and development (e.g., Liebmann et al ., ; Maloney and Hartmann, ; Huang et al ., ; Cao et al ., ; Zhao et al ., ). Liebmann et al .…”
Section: The Changes In the Higher‐frequency Activitymentioning
confidence: 99%
“…Extended empirical orthogonal function (EEOF) analysis (Weare and Nasstrom, ) is used in this study to extract the ISO modes, following previous studies (Jiang and Waliser, , ; Jiang et al ., ; Zhao et al ., , , 2016; Neena et al ., 2017). EEOF analysis of the daily 10‐ to 30‐day band‐pass filtered TRMM rainfall anomalies during the boreal summer for the period 1998–2015 is performed (as in Jiang et al .…”
Section: Methodsmentioning
confidence: 99%
“…() and Zhao et al . (, )), with temporal lags of 9 days over the following domain: (0°–30°N, 140°–90°W). The boreal summer QBWO mode over the ENP basin is identified by the first leading pair of EEOF modes (Figure ), as shown in Jiang and Waliser (, ).…”
Section: Methodsmentioning
confidence: 99%